Prevalence and influencing factors of lower urinary tract symptoms in female nurses: a cross-sectional study based on TARGET - Zhang, Xinyue; Li, Mengli; Dong, Wenshuo; Lv, Xiaoyan; Li, Li; Yang, Xiaorong; Cao, Yingjuan (Frontiers in Public Health, 2023)
Background Even though occupational women have a high incidence of lower urinary tract symptoms (LUTS), which seriously affect their daily work life, few large scale sample studies have provided empirical evidence to support this phenomenon among female nurses in China. Consequently, this article investigated female nurses who was presupposed to have a high prevalence of LUTS, which adversely exposes their health and patient safety to these risks. Additionally, it is considered important to explore the factors associated with LUTS in female nurses for patient care safety and nurse bladder health practice. Objectives The purpose of this study was to assess the incidence of LUTS and symptoms-related risk factors among female nurses, to provide evidence for the prevention and control of LUTS. Methods An online survey recruiting 23,066 participants was carried out in a multicenter cross-sectional study in 42 hospitals from December 2020 to November 2022. Stepwise multivariate logistic regression analysis and nomogram were used to identify the factors associated with lower urinary tract symptoms. Besides, SPSS version 26.0, R version 4.2.2, and GraphPad Prism Version 8.3 software packages were used for statistical analysis. Results Based on the completion rate of the questionnaire which was 84.1% (n = 19,393), it was found that among 19,393 female nurses, the prevalence of LUTS was 67.71% and this rate was influenced by age, Body Mass Index (BMI), marital status, years of working, menstrual status, mode of delivery, history of breastfeeding, history of miscarriage, history of alcohol and coffee or tea consumption (p < 0.05). Interestingly, we also find that in addition to the above mentioned factors, anxiety, depression, and perceived stress were also related to LUTS in female nurses (p < 0.05). Conclusion Given the high prevalence of LUTS among female nurses and their potential influencing factors, female nurses should focus on their reproductive health and develop good lifestyle habits. Thus, nursing managers should provide a warm and harmonious work environment and sensitize female nurses to increase their awareness about the importance of drinking clean water and urinating during work in a hygienic environment.